Teologi Islam: dari Teologi Klasik hingga Teologi Kontemporer - sarkowi, sarkowi (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2018)
Building construction of the contemporary theology concept should regard to the conventional theologians. The contemporary theologians tradition will not meet a power when they do not have a strong knowledge relation to the classic ones. This understanding states that lingkages between the continous principle of the last thought and the today and future updates is formulated in terms of al-muhafadhah ‘ala al-qadim salih wa akhd bi al-jadid al-aslah (mantaining the good old ones and take the better new ones). Through the formula, the contemporary theology will make Islamic teachings function effectively in dinamic and upheaval modern societies. Keywords: Islamic Theology, Classic Theology, Cemtemporary Theology